Challenges Faced by Social Workers Handling Violence Against Women and Their Children - Balog, Gemmalyn (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the challenges encountered by social workers in handling Violence Against Women and Their Children (VAWC) cases within the culturally distinct context of Ifugao Province. Anchored in Bronfenbrenner’s Ecological Systems Theory and Lazarus and Folkman’s Transactional Model of Stress and Coping, the study utilized a qualitative case study design (Yin, 2018) to explore how institutional, cultural, and legal factors shape social workers’ experiences. Data were collected through in-depth, semi-structured interviews with five purposively selected registered social workers serving as VAWC focal persons in the Municipal and Provincial Social Welfare and Development Offices. Thematic analysis following Braun and Clarke (2019) was employed to identify patterns within the data. Findings revealed six major challenges: workload and staffing constraints, emotional toll and professional strain, cultural norms and informal justice practices, threats and safety risks, procedural and legal system barriers, and institutional and resource constraints. These challenges collectively affect the timeliness, quality, and continuity of VAWC interventions. Cultural practices such as informal settlements were found to intersect with formal legal systems, influencing case outcomes and victim participation. Emotional strain and safety risks further impact the well-being and effectiveness of social workers. The study concludes that these challenges are interconnected and structurally embedded, requiring strengthened institutional support, culturally responsive approaches, and protective mechanisms. It recommends improving workforce capacity, institutionalizing psychosocial support, enhancing inter-agency coordination, strengthening safety protocols, and increasing resource allocation. The study aligns with Sustainable Development Goals SDG 5 (Gender Equality), SDG 3 (Good Health and Well-Being), and SDG 16 (Peace, Justice, and Strong Institutions) by addressing gender-based violence, promoting well-being, and strengthening justice systems. It contributes to socio-economic, institutional, and community sustainability by improving service delivery systems and supporting the well-being of frontline social workers in culturally complex settings.
Keywords: Case Study Design; Ifugao Province; Social Workers; Thematic Analysis; VAWC Case Management; Violence Against Women and Children